PREVALENCE OF NON ALCOHOLIC FATTY LIVER DISEASE IN PATIENTS WITH METABOLIC SYNDROME: Non Alcoholic Fatty Liver Disease - Iftikhar, Raheel; Kamran, Sultan Mehmood; Sher, Farrukh; Wahla, Madiha Saeed (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine frequency of Non Alcoholic fatty liver disease in patients with Metabolic Syndrome (MetS).Study Design: Cross sectional study.Place and Duration of Study: Department of medicine, CMH Okara, Jan 2013 to July 2013.Patients and Methods: We included 491 adult males, diagnosed with metabolic syndrome (MetS), presenting in outpatient department for routine review. MetS was diagnosed as per the International Diabetes Federation (IDF) proposed criteria of 2004. Detailed history and examination of each individual was done and data entered in pre designed performa. Brightness and posterior attenuation on ultrasound abdomen were considered indices for fatty liver disease in presence of elevated ALT, negative hepatitis serology and absence of alcohol intake. All the data was analyzed using SPSS version 16. p value of less than 0.05 was considered statistically significant.Results: Out of 491 participants with MetS, 222 (45.2%) had fatty liver disease. Mean BMI in patients with metabolic syndrome was 26.1 (± .89) and mean BMI in fatty liver patients was 27.3 (± 0.67).Out of total 5 components of Mets, patients with fatty liver disease had 3.24 (± 0.25) components, as compared to 2.1 (± 0.34) in whole of study group.Conclusion: A large number of patients with metabolic syndrome have fatty liver disease. Fatty liver disease is more frequent in patients who are overweight and those having multiple risk factors of metabolic syndrome.